Edukasi Pemanfaatan Biopestisida dari Umbi Bawang Putih Sebagai Alternatif Pengendalian OPT Ramah Lingkungan di Grand Puri Bunga Nirwana, Jember - Anindita, Devina Cinantya; Arisandi, Dewi Puspa; Adnyani, Ni Nengah Putri; Sabiku, Dewi Fatmawaty; Alfiah, Nur Aini; Fadilah, Anggita Rizky; Nur, Ferril Muhammad (Kadiri University, 2025)
Household food self-sufficiency can be achieved by utilizing home yards for cultivating vegetables such as pakcoy, spinach, chili, and tomatoes. However, vegetable crops are generally susceptible to pest attacks if not properly maintained. One environmentally friendly and health-safe solution for pest control is the use of botanical pesticides. This community service activity aimed to increase the knowledge and skills of housewives in making and using botanical pesticides based on garlic as an alternative method of pest control. The program was conducted at the Grand Puri Bunga Nirwana residential area and involved housewives interested in home gardening. The methods used included educational sessions and hands-on demonstrations on how to make botanical pesticides—covering the selection of ingredients, preparation process, and application techniques. The results showed that participants experienced an increase in understanding of natural pest control and improved skills in independently producing botanical pesticides. The enthusiasm of the participants also indicated a strong interest in applying the knowledge gained to their daily gardening practices. Through this activity, it is expected that housewives will become more independent and sustainable in maintaining the health of food crops in their home gardens. Kemandirian pangan rumah tangga dapat diwujudkan melalui pemanfaatan lahan pekarangan untuk budidaya tanaman sayuran seperti pakcoy, bayam, cabai, dan tomat. Namun, tanaman sayuran umumnya rentan terhadap serangan hama jika tidak dirawat secara optimal. Salah satu solusi pengendalian hama yang ramah lingkungan dan aman bagi kesehatan adalah dengan penggunaan pestisida nabati. Pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan keterampilan ibu rumah tangga dalam membuat dan menggunakan pestisida nabati berbahan dasar bawang putih sebagai alternatif pengendalian hama. Kegiatan dilaksanakan di Perumahan Grand Puri Bunga Nirwana dan diikuti oleh para ibu rumah tangga yang memiliki minat terhadap pertanian pekarangan. Metode yang digunakan dalam kegiatan ini meliputi penyuluhan dan demonstrasi langsung pembuatan pestisida nabati, mulai dari pemilihan bahan, proses pembuatan, hingga cara aplikasi pada tanaman. Hasil kegiatan menunjukkan bahwa para peserta mengalami peningkatan pemahaman mengenai pentingnya pengendalian hama secara alami serta keterampilan dalam meracik pestisida nabati secara mandiri. Antusiasme peserta juga menunjukkan adanya minat untuk menerapkan hasil sosialisasi dalam kegiatan berkebun mereka sehari-hari. Dengan adanya kegiatan ini, diharapkan ibu rumah tangga dapat lebih mandiri dan berkelanjutan dalam menjaga kesehatan tanaman pangan di pekarangan rumah.